Effect of silicon soluble association with fungicide in coffee (Coffea arabica L.) crop disease and pest control - Reis, Thiago Henrique Pereira; Figueiredo, Felipe Campos; Guimarães, Paulo Tácito Gontijo; Botrel, Priscila Pereira; Rodrigues, Carlos Ribeiro (Coffee Science - ISSN 1984-3909, 1970)
Soluble silicon and fungicide mixed were evaluated to control coffee (Coffea arabica L.) pests and diseases. This experiment was carried out in Três Pontas-MG, Brazil, Mundo Novo cultivar crop. The experimental design was randomized blocks with treatments like: soluble silicon 4L/ha; soluble silicon 3L/ha + fungicide 0,375L/ha; soluble silicon 2L/ha + fungicide 0,75L/ha; soluble silicon 1L/ha + fungicide 1,125L/ha; fungicide 1,5L/ha and control without pulverization. Half silicon soluble recommended dose associated with half fungicide recommended dose was efficient to control coffee leaf rust and coffee brown eye spot like fungicide recommended full dose.